Cadaveric simulation versus standard training for postgraduate trauma and orthopaedic surgical trainees: protocol for the CAD:TRAUMA study multicentre randomised controlled educational trial. Issue 9 (25th September 2020) - James, Hannah K; Pattison, Giles T R; Fisher, Joanne D; Griffin, Damian
Abstract : Introduction: The quantity and quality of surgical training in the UK has been negatively affected by reduced working hours and National Health Service (NHS) financial pressures. Traditionally surgical training has occurred by the master-apprentice model involving a process of graduated responsibility, but a modern alternative is to use simulation for the early stages of training. It is not known if simulation training for junior trainees can safeguard patients and improve clinical outcomes. This paper details the protocol for a multicentre randomised controlled educational trial of a cadaveric simulation training intervention versus standard training for junior postgraduate orthopaedic surgeons-in-training. This is the first study to assess the effect of cadaveric simulation training for open surgery on patient outcome. The feasibility of delivering cadaveric training, use of radiographic and clinical outcome measures to assess impact and the challenges of upscaling provision will be explored. Methods and analysis: We will recruit postgraduate orthopaedic surgeons-in-training in the first 3 years (of 8) of the specialist training programme. Participants will be block randomised and allocated to either cadaveric simulation or standard 'on-the-job' training, learning three common orthopaedic procedures, each of which is a substudy within the trial. The procedures are (1) dynamic hip screw, (2) hemiarthroplasty and (3) ankle fracture fixation. These procedures have been selected as they are very common procedures which are routinely performed by junior surgeons-in-training. A pragmatic approach to sample size is taken in lieu of a formal power calculation as this is novel exploratory work with no a priori estimate of effect size to reference. The primary outcome measure is the technical success of the surgery performed on patients by the participating surgeons-in-training during the follow-up period for the three substudy procedures, as measured by the implant position on the postoperative radiograph. The secondary outcome measures are procedure time, postoperative complication rate and patient health state at 4 months postoperation (EQ-5D—substudies 1 and 2 only). Ethics, registration and dissemination: National research ethics approval was granted for this study by the NHS Research Authority South Birmingham Research Ethics Committee (15/WM/0464). Confidentiality Advisory Group approval was granted for accessing radiographic and outcome data without patient consent on 27 February 2017 (16/CAG/0125). The results of this trial will be submitted to a peer-reviewed journal and will inform educational and clinical practice. Trial registration number: ISRCTN20431944